Infant regulatory problems and the quality of dyadic emotional connection—a proof-of-concept study in a multilingual sample - Jaekel, Julia; Dathe, Anne-Kathrin; Brasseler, Maire; Bialas, Johanna; Jokiranta-Olkoniemi, Elina; Reimann, Margarete; Ludwig, Robert J.; Hane, Amie A.; Welch, Martha G.; Huening, Britta M. (Frontiers in Child and Adolescent Psychiatry, 2024)
Background and aims Close autonomic emotional connections with others help infants reach and maintain homoeostasis. In recent years, infant regulatory problems (RPs, i.e., crying, sleeping, and feeding or eating problems) have surged. This study has two aims: (1) Provide proof-of-concept that dyadic autonomic emotional connection between infants and parents can be reliably assessed with a brief screening, irrespective of language and culture. (2) Assess in a heterogeneous pilot sample whether the persistence of RPs during infancy is negatively associated with the quality of dyadic autonomic emotional connection. Methods 30 children aged 3–68 months (47% female) and their parents (83% mothers) were assessed during regular neonatal follow-up visits in Germany. Seven (23%) dyads were immigrants whose primary language was not German. At each assessment, paediatricians asked parents about infant's crying, sleeping, and feeding or eating problems. Dyadic interactions were rated by a multilingual team with the standardised universal Welch Emotional Connection Screen (uWECS) on four dimensions (attraction, vocalisation, facial communication, sensitivity/reciprocity). Results Aim 1: An international team of raters was trained remotely to rate the uWECS. Reliability of α > .90 with standard raters was achieved irrespective of language mismatches (i.e., all raters scored several videos with languages they did not understand). Intra-class correlation coefficients (ICCs) among five main raters for the four uWECS dimensions ranged from .98–.99. Aim 2: Infants (n = 15 assessed longitudinally) had mean RP scores of 1.20 (SD = 1.26). Dyads had mean uWECS scores of 7.06 (SD = 2.09). Linear regression analysis showed that more persistent RPs in infancy were associated with lower uWECS scores [β = -.53, 95% CI = (-1.47, -.18), p = .017], after controlling for child sex and gestational age. Conclusion This study provides proof-of-concept that the quality of mutual autonomic emotional connection among socio-culturally and linguistically heterogeneous samples can be reliably assessed with the uWECS, a brief screening that can be easily implemented in clinical practice. Pilot data suggests that persistent RPs during infancy are negatively associated with the quality of dyadic autonomic emotional connection. Replication of these findings in larger samples is warranted. Future studies need to address how to facilitate successful emotion regulation for today's children and future generations.